Cross - Century Discovery: Mendelian Dualistic Genetics (Global Journal of Science Frontier Research, 2022)
This article is a summary and review of new insights into Mendel's gene assumption since its rediscovery in 2018. This is a cross-century discovery. The gene assumption told the world that the gene is the element that makes individuals being with parental specifications. The gene is the facilitator rather than the producer. New individuals with parental specifications are produced by the facilitator and its recipient in cooperation. This is conceptually roughly the same as making airplanes with two elements, the drawing and the production line. Thus, the hereditary material should consist of two elements; genetics is dualistic. T.H. Morgan, who founded the theory of the gene and regarded the gene as the producer of individuals, completely misunderstood Mendel, and pulled Mendelian genetics back into the mire of monism. O.T. Avery et al. confirmed that genes are DNA, thereby ushering in the era of the physical verification of the truth of genes. The scientific facts gathered in later 60 years finally prove that any individual, animal or plant (including single-celled organisms), is the product of the transcription of its DNA (genome) by the transcriptase (system) of an egg. In other words, the hereditary material able to give rise to the individuals consists of egg transcriptase (system) and DNA (genome).
Keywords: genes; hereditary material; genetics; template; transcriptase